Diagnóstico da saúde ambiental no território de abrangência da UBSF - Jardim Europa da cidade de Uberlândia, Minas Gerais - Silva, Marina Maria Eliete da (2019)
The expansion of the cities' peripheries is one of the many consequences of urban growth. In these places, not infrequently occupied by the low-income population, the occurrence of problems related to environmental sanitation and the socioeconomic situation tends to contribute to the emergence of several diseases that, gradually, compromise the quality of life of its inhabitants. In this sense, this study aimed to analyze the environmental health conditions in the UBSF territory of the Jardim Europa I, a neighborhood in the city of Uberlândia / MG, and its relationship with the health of its population. For that, initially, a theoretical framework was elaborated on the thematic centered on the process of urban peripheralization, environmental health, Unified Health System and territorialization of health. In operational terms, data were collected at the UBSF in order to identify the number of users, sex, main reasons for searching the BFHU, diseases with higher occurrences and period of higher prevalence. In the scope of the UBSF, field observations were made through on-site visits for the recognition of environmental conditions and photographic records. To identify the population, questionnaires were applied to UBSF users and residents of the neighborhood, containing dimensions of the social aspects, the living environment, and the neighborhood. Data analysis showed that the most prevalent schooling is full secondary education and the main reasons for searching the BFHU are consultations, examinations and vaccination. Concerning the environmental-related discomforts, burns, garbage on vacant lots and in inappropriate places should be highlighted. Concerning the morbidities that affected the participants in the analyzed period, these were cough, diarrhea and allergy. This study concludes that there is an urgent need for the development and implementation of public policies that aim to improve the neighborhood's environmental conditions, not only for environmental care but also for improving the health of the population.